2011
DOI: 10.4314/bajopas.v3i2.63209
|View full text |Cite
|
Sign up to set email alerts
|

Effect and Management of acute dichlovos poisoning in Wistar Rats

Abstract: Dichlorvos; organophosphorus pesticide is among the most widely used pesticides for insect control. In Nigeria and most other developing countries it is used indiscriminately by people with little or no knowledge of its toxic effects as a household and agricultural insecticide. The acute effect and antidotal therapy of dichlorvos was studied in laboratory animals. The LD 50 in rats was determined to be 28.28 mg/kg i.p, with acute poisoning symptoms of micturation, restlessness, pupil constriction, respiratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 5 publications
(7 reference statements)
3
8
2
Order By: Relevance
“…This finding is consistent with those reported by Yurumez et al, and that of Chedi and Aliyu. 13,14 Though the centrally acting α2-adrenergic receptor agonists such as clonidine can reduce Ach synthesis and release in pre-synaptic junction and has a protective effect against the centrally acting AchE, but in our study the rats which received only clonidine has shown significant (p<0.05) improvement central effects only for straubs tail and whole body tremors compared to that of control and atropine with clonidine group. But our study results are similar with the study by Buccafusco and Aronstam 1986 that pre-treatment with clonidine protected against several of the centrally-mediated toxic effects of soman.…”
Section: Discussioncontrasting
confidence: 63%
“…This finding is consistent with those reported by Yurumez et al, and that of Chedi and Aliyu. 13,14 Though the centrally acting α2-adrenergic receptor agonists such as clonidine can reduce Ach synthesis and release in pre-synaptic junction and has a protective effect against the centrally acting AchE, but in our study the rats which received only clonidine has shown significant (p<0.05) improvement central effects only for straubs tail and whole body tremors compared to that of control and atropine with clonidine group. But our study results are similar with the study by Buccafusco and Aronstam 1986 that pre-treatment with clonidine protected against several of the centrally-mediated toxic effects of soman.…”
Section: Discussioncontrasting
confidence: 63%
“…Their detection was not surprising as they are commonly used as post harvest pesticides on kola nut in the study area. The presence of these pesticides residue in kola nut could be attributed to the inappropriate application such as over dosage of the said pesticides and indiscriminate acts to achieve set goals (Chedi et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Improper use of pesticide may result in high Pesticide residue above the EUMRLs that will be hazardous to the consumer and lead to the emergence of resistant pest populations which would be insensitive to normal pesticide dosage (Chedi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…To protect stored rice from pest infestation, farmers and post-harvest handlers in Nigeria rely heavily on the use of chemicals [8]. The organophosphate Dichlorvos (dichlorovinyl dimethyl phosphate-DDVP) is one of the commonest insecticides available for use in Nigeria [8][9][10][11]. Due to the low level of literacy among farmers and merchants handling pesticides in Nigeria, application at a rate higher than the manufacturer's specification is inevitable.…”
Section: Introductionmentioning
confidence: 99%